2015
DOI: 10.1007/s11606-015-3327-1
|View full text |Cite
|
Sign up to set email alerts
|

From Public to Social Reporting of Hospital Quality

Abstract: M ore than a quarter-century has passed since the Centers for Medicare and Medicaid Services (CMS) published their first Breport cards^on hospital mortality data. 1 While this initial attempt at public reporting suffered from methodological flaws and was ended in 1993, 2 it represented the beginning of a huge international experiment. This experiment is ongoing and is still pondering the question: BCan providing publicly available information about health care quality direct patient choice of health care provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The discrepancy between the typical patient survey and other data sources demonstrates the need to use other data sources to ascertain public sentiment about healthcare services [ 17 ]. Therefore, the internet in general and social media in particular have been suggested as new tools for evaluating patient satisfaction and monitoring the quality of healthcare services [ 7 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy between the typical patient survey and other data sources demonstrates the need to use other data sources to ascertain public sentiment about healthcare services [ 17 ]. Therefore, the internet in general and social media in particular have been suggested as new tools for evaluating patient satisfaction and monitoring the quality of healthcare services [ 7 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though these surveys are conducted in a systematic manner and capable of capturing a significant number of patient responses in a given hospital, they are expensive to implement, time intensive, and suffer from poor response rates and other challenges [ 2 , 5 ]. Thus, the internet, and social media specifically, has been proposed as a method of complementing or replacing traditional methods of assessing patient satisfaction and monitoring the quality of healthcare services [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has been evidenced in a German study that showed how doctors who read their negative reviews and also responded to them, make an effort to improve the aspects that were criticized in their work [ 47 ]. Hence, the need for the public to be involved in quality of care reporting is increasingly suggested [ 49 , 50 ]. Yet, the assurance of quality and content on PRWs asks for further research and knowledge translation into practice.…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, Facebook is extensively utilized, and its market share continues to rise and in 2020, Facebook was the country’s most popular social networking site [ 20 ]. Facebook reviews is a technology that allows people to provide narrative reviews on organizations’ Facebook pages, and the feature offers insight into how the public perceives healthcare services [ 21 ]. Few studies have been conducted in the past to evaluate Facebook reviews of hospital services and nursing homes and found a low to moderate correlation between Facebook ratings and patient satisfaction metrics from systematic surveys [ 18 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%